Bibliometric Mapping of Meteorological Conditions and Covid-19 Transmission Based On Vosviewer - Fajar Supramono; Jhons Fatriyadi Suwandi; Dewi Agustina Iryani; Samsul Bakri (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this study is that all research articles in journals discussing meteorology related to this research are to find out the form of mapping research subjects in journals discussing meteorology associated with COVID-19 transmission based on the database. Google Scholar and Scopus. The method used is descriptive research by doing research mapping. The research mapping in question is a literature study using bibliometrics. The bibliometric method aims to classify and interpret statistics related to scientific publications. Unit of analysis p with COVID-19 transmission based on database Google Scholar and Scopus since the COVID-19 pandemic until the end of 2021. The results of this study show an overview of the publication trend between meteorological conditions and confirmed cases of COVID-19 until the end of 2021, indicating that this variable is still rarely studied. This can be seen from the nets connecting the meteorological condition variables with the COVID-19 variable, which still looks far away. In addition, the diameter that describes the meteorological condition variable is still small, which means there is still a lot of room for researchers to conduct research related to the meteorological condition variable with the COVID-19 variable.